Optimization of AI Use for Pedagogical Strategies in Virtual University Environments in Ecuador: ICT and Teacher Training - Quintuña Zambrano, Katherine; Arguello, Mario (Scripta Mundi, 2026)
This study addresses the issue of the lack of systemic integration of artificial intelligence (AI) in the pedagogical strategies of Ecuadorian universities, which limits its impact on student learning. The objective of the research was to evaluate how the use of AI-based tools, along with Information and Communication Technologies (ICT), could improve academic performance and student motivation in virtual environments. A mixed methodology was used, combining quantitative data through a Likert-type questionnaire and qualitative data through interviews with professors, with a sample of 80 students and 20 professors from three Ecuadorian universities.The main results indicate that virtual assistants, automatic translators, and grammar checkers were the most used tools. These tools had a positive impact on motivation (85%), content comprehension (82%), and personalized learning (80%). Additionally, a significant correlation was found between the frequent use of AI and students’ academic performance.This study highlights that the implementation of AI in teaching strategies can improve motivation, participation, and academic performance. However, its effectiveness depends on continuous teacher training, equitable access to technology, and clear institutional policies.